蜗杆机构复合应用实例分析 - 杨萍 (Jixie chuandong)
Base on the involutes worm principle,According to design requirement, involutes worm is used in the thread machine-feeding device.The involutes worm function is transferring cutting-movement and power.The movement relation and theory transmission error of the thread machine-feeding device are analyzed.There is a certain reference value to the complex application of involutes worm.